Adjustment of Food Textural Properties for Elderly Patients. Issue 4 (4th July 2016) - Cichero, J.A.Y.
Abstract: Over the next twenty years the number of people over 60 years will exceed one billion. Changes associated with ageing have an impact on food texture choices for healthy elders and those used therapeutically for people with swallowing difficulties (dysphagia). The ideal "swallow‐safe" bolus is moist, cohesive and slippery. A general reduction in muscle strength is seen throughout the ageing oropharyngeal musculature, resulting in a reduced ability to safely and efficiently manage hard or fibrous textured foods. Reduced masticatory ability combined with dental loss further compounds the issue. Dry mouth is commonly associated with old age, making it difficult to propel dry or sticky textures through the pharynx, and increases the likelihood of pharyngeal residue. An age related reduction in laryngopharyngeal sensitivity dampens the ability to detect residue, increasing choking risk. Reduced tongue pressure, increases in pharyngeal transit time, valleculae residue, number of clearing swallows and slower and less efficient oesophageal transit occur with aged swallowing. Food textures that are sticky and adhesive will require increased lingual effort to propel them into and through the pharynx. Taken in combination these factors mean that food textures prescribed to the elderly need to be soft and moist and for fibers to be easily broken. To improve moisture content, additional nutrient dense products (e.g., milk, cream or butter) may be required to artificially moisten the bolus. Careful, individualized attention to diet recommendations will result in a diet that is appealing and also provide a variety of textures that are swallow‐safe and nutrient dense. Practical Application: Aged related changes in the oral cavity and the oral, pharyngeal and oesophageal phases of swallowing require special thought to the suitability of food textures for the elderly. Foods that are fibrous, hard or dry may be unsuitable due to difficulties with safe particle size reduction and bolus formation for swallowing. Foods that are sticky and adhesive are also problematic and increase risk for both choking and residue. Food texture properties that are ideally suited for the elderly include those that are soft, moist, and easily reduced with minimal chewing effort. Hard food textures that break down and dissolve easily with minimal chewing should be investigated. Increased aroma and flavor may improve appeal lost through reduced variety in food textures. Diet reviews need to consider both textures that can be safely managed and the nutrient density of those textures.